COVID-19: THE SCAPEGOAT FOR THE EMPLOYERS - Vinesh Raj S; Meghna Gohain, (International Journal on Recent Trends in Business and Tourism (IJRTBT), 2021)
Coronavirus Disease (COVID-19) is a respiratory infectious disease caused by a new strain of virus. The pandemic infection started in the province of Wuhan, China at the end of 2019 and within 3 months it spread as wildfire to more than 200 countries. Every day on the news there has been an update of increase in numbers of people being tested positive for COVID-19 virus. To combat COVID-19, policy makers worldwide have adopted different policy alternatives, often including mitigation/suppression policies. These in turn had a profound impact on the world economy. This situation has led to financial instability of many organizations as well. The employers are put in a dilemma to overlook the well-being of the organization and benefits of the employee. The employers seem to take advantage of this crisis towards their employee. When looking at the history of human civilization, finding a scapegoat to blame for a pandemic is nothing new. Employees were forced to resign/ leave or even terminated for voicing concerns about the lack of health and safety protocols. Employees were laid off ostensibly because of COVID-19. However, something more nefarious and worse is discrimination against certain group of ethnicities.